Acidophilic denitrifiers dominate the N2O production in a 100-year-old tea orchard soil - Huang, Ying; Long, Xi-En; Chapman, Stephen J; Yao, Huaiying (Environmental science and pollution research international, 2015)
Aerobic denitrification is the main process for high N₂O production in acid tea field soil. However, the biological mechanisms for the high emission are not fully understood. In this study, we examined N₂O emission and denitrifier communities in 100-year-old tea soils with four pH levels (3.71, 5.11, 6.19, and 7.41) and four nitrate concentration (0, 50, 200, and 1000 mg kg⁻¹of NO₃⁻-N) addition. Results showed the highest N₂O emission (10.1 mg kg⁻¹over 21 days) from the soil at pH 3.71 with 1000 mg kg⁻¹NO₃⁻addition. The N₂O reduction and denitrification enzyme activity in the acid soils (pH <7.0) were significantly higher than that of soils at pH 7.41. Moreover, TRF 78 of nirS and TRF 187 of nosZ dominated in soils of pH 3.71, suggesting an important role of acidophilic denitrifiers in N₂O production and reduction. CCA analysis also showed a negative correlation between the dominant denitrifier ecotypes (nirS TRF 78, nosZ TRF 187) and soil pH. The representative sequences were identical to those of cultivated denitrifiers from acidic soils via phylogenetic tree analysis. Our results showed that the acidophilic denitrifier adaptation to the acid environment results in high N₂O emission in this highly acidic tea soil.